PENATALAKSANAAN FISIOTERAPI PADA KONDISI DEVELOPMENT DELAYED (DD) DENGAN METODE HIDROTERAPI HUBBARD TANK DAN GENERAL MASSAGE DI YPAC SURAKARTA - Antonius Adi Susanto; Nur Susanti (LPPM Universitas Pekalongan, 2020)
Development delayed (DD) is a condition where the pace on the physical, emotional, behavioral and social development. When compared with normal child his age. Problematic conditions delayed development (DD) is a decrease in postural tone, muscle weakness, disruptions in functional capabilities. Handling is done in case of delayed development (DD) is a growth by DDST examination, examination of muscle strength and postural tone with XOTR scale, sensory examination, and functional capabilities with GMFM.In addressing the problem of delayed development conditions (DD) by the method of Hubbard tank hydrotherapy and general massage. The design of the research this scientific paper uses case studies drawn in Surakarta YPAC. After six times of therapy by using the technology intervention and general massage Hubbard tank obtained the following results (1) for growth and development remain the same, namely T1 to T6 = 12 aspects of personal sector gross motor and social late eighth aspects, (2) an increase in muscle strength and postural tone for the wrist, hip, knee, and ankle T1 = T at T4 = X, (3) there is an increase for the sensory examination of the T4 to T6 namely touch, tactile and vestibular propioseptive but there is no improvement (4) the improvement of functional ability T1 = 67% to T6 = 84.6%.From the results obtained, it can be concluded that the use of physiotherapy intervention with Hubbard tank hydrotherapy and General Massage can reduce the problem of delayed development conditions (DD).